Analisis Bibliometrik Tren Perkembangan Penelitian dan Publikasi Mengenai Beauty Privilege (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to explore the trends in the development of scientific publications on beauty privilege, focusing on the growth in the number of articles, citation trends, as well as keyword mapping and the dominant themes emerging in the literature. The method used is a literature review with a descriptive bibliometric approach, referring to the PRISMA model which includes four stages: identification, screening, eligibility, and inclusion. Data were collected from Google Scholar using the Publish or Perish (PoP) software, with the keyword “beauty privilege.” The analysis results show that the number of publications has increased significantly since 2021, peaking in 2023 and 2024. In terms of citations, 2023 is the most influential year, having the highest number of citations. Keyword analysis using VOSviewer generated seven topic clusters, with dominant keywords such as beauty privilege, body shaming, and social media. The conclusion of this study indicates that the topic of beauty privilege is becoming increasingly relevant and evolving, opening opportunities for further research from various social, cultural, and psychological perspectives.